Struktur Komunitas Makrozoobentos di Estuaria Kuala Sugihan Provinsi Sumatera Selatan - Irmawan, Rizky Nurul; Zulkifli, Hilda; Hendri, Muhammad (Maspari Journal : Marine Science Research, 2010)
Researches on the spatial distribution of sediment characteristics and community structure of macrozoobenthos have been executed on November 17th to 20th 2009 in Kuala Sugihan estuaries. The purpose of this study is, to measure water quality, study the spatial distribution of sediment characteristics, knowing the structure of macrozoobenthos communities and study the spatial distribution of macrozoobenthos in estuaries Kuala Sugihan. Data analysis was done of macrozoobenthos community structure analysis performed by determining the value of diversity index (H'), uniformity index (E) and dominance index (C) species. The research that physical-chemical water parameters measured showed values that are still at the threshold quality standard that allowed for marine life (KLH Ministerial Decree No. 51 of 2004). Caracteristics (physics-chemistry) in estuarine sediments Kuala Sugihan showed that sediment texture of clay to the clay berliat and dusty clay is a suitable habitat for life and affect the density of macrozoobenthos and species composition of each observation station. Macrozoobenthos found in estuarine waters of Kuala Sugihan as many as 21 species included in four classes Polychaeta (nine species), gastropods (nine species), Bivalvia (2 species) and crustaceans (one species). Diversity index (H') at the study sites were the highest 3.238. Station 1 is located on the inside of the mouth is found only one type of spatial Polychaeta. Keywords: Kuala Sugihan Estuarine and Makrozoobenthos Penelitian mengenai struktur komunitas makrozoobentos telah dilaksanakan pada tanggal 17-20 November 2009 di estuaria Kuala Sugihan. Tujuan penelitian ini yaitu, mengukur kualitas perairan, mengukur kualitas sedimen dan mengetahui struktur komunitas makrozoobentos dan mempelajari sebaran spasial makrozoobentos di estuaria Kuala Sugihan. Analisis data yang dilakukan yaitu analisa struktur komunitas makrozoobentos dilakukan dengan menentukan nilai indeks keanekaragaman (H’), indeks keseragaman (E) dan indeks Dominansi (C) spesies. Hasil penenlitian bahwa parameter fisika-kimia air yang terukur menunjukkan nilai-nilai yang masih berada pada ambang batas baku mutu yang diperbolehkan bagi kehidupan biota laut (Kepmen KLH No. 51 Tahun 2004). Karakteristik (fisika-kimia) sedimen di estuaria Kuala Sugihan menunjukkan bahwa tektur sedimennya berupa lempung ke arah lempung berliat dan lempung berdebu merupakan habitat yang cocok bagi kehidupan makrozoobentos dan berpengaruh kepada kepadatan serta komposisi jenis dari setiap stasiun pengamatanMakrozoobentos yang ditemukan di perairan estuaria Kuala Sugihan sebanyak 21 jenis yang termasuk di dalam 4 kelas yaitu Polychaeta (9 jenis), Gastropoda (9 jenis), Bivalvia (2 jenis) dan Crustacea (1 jenis). Nilai indeks keanekaragaman jenis (H’) pada lokasi penelitian yang tertinggi yaitu 3,238 dan yang terendah yaitu 0. Stasiun 1 yang berada di bagian dalam muara hanya ditemukan satu jenis dari kelas Polychaeta. Kata kunci : Estuaria Kuala Sugihan dan makrozoobentos